2022
DOI: 10.1155/2022/2351779
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Framework of Major Power Project Management Based on System Thinking

Abstract: Major power projects are normally critical nodes of the national power producing and transmission networks. However, the management of major power projects faces a variety of difficulties such as large scale, technical complexity, high quality standard, and frequent coordination. To improve the scientificity and effectiveness of the construction management of major power projects, a comprehensive framework of major power projects is established, which can be further decomposed into 8 subsystems and 28 indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Zhu et al [42] concluded that power projects adopt system thinking and establish a framework for high-quality standards to meet the requirement of sustainability construction elements. This study finds the same conclusion as Zhu et al that quality must be the primary concern for building a logistics center for SPPS.…”
Section: Research Conclusionmentioning
confidence: 99%
“…Zhu et al [42] concluded that power projects adopt system thinking and establish a framework for high-quality standards to meet the requirement of sustainability construction elements. This study finds the same conclusion as Zhu et al that quality must be the primary concern for building a logistics center for SPPS.…”
Section: Research Conclusionmentioning
confidence: 99%